Decompressive Surgery in Cerebral Venous Sinus Thrombosis Due to Vaccine‐Induced Immune Thrombotic Thrombocytopenia - Krzywicka, K (2023)
Background and purpose: Cerebral venous sinus thrombosis due to vaccine-induced immune thrombotic thrombocytopenia (CVST-VITT) is an adverse drug reaction occurring after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. CVST-VITT patients often present with large intracerebral haemorrhages and a high proportion undergoes decompressive surgery. Clinical characteristics, therapeutic management and outcomes of CVST-VITT patients who underwent decompressive surgery are described and predictors of in-hospital mortality in these patients are explored. Methods: Data from an ongoing international registry of patients who developed CVST within 28 days of SARS-CoV-2 vaccination, reported between 29 March 2021 and 10 May 2022, were used. Definite, probable and possible VITT cases, as defined by Pavord et al. (N Engl J Med 2021; 385: 1680-1689), were included. Results: Decompressive surgery was performed in 34/128 (27%) patients with CVST-VITT. In-hospital mortality was 22/34 (65%) in the surgical and 27/94 (29%) in the non-surgical group (p < 0.001). In all surgical cases, the cause of death was brain herniation. The highest mortality rates were found amongst patients with preoperative coma (17/18, 94% vs. 4/14, 29% in the non-comatose; p < 0.001) and bilaterally absent pupillary reflexes (7/7, 100% vs. 6/9, 67% with unilaterally reactive pupil, and 4/11, 36% with bilaterally reactive pupils; p = 0.023). Postoperative imaging revealed worsening of index haemorrhagic lesion in 19 (70%) patients and new haemorrhagic lesions in 16 (59%) patients. At a median follow-up of 6 months, 8/10 of surgical CVST-VITT who survived admission were functionally independent. Conclusions: Almost two-thirds of surgical CVST-VITT patients died during hospital admission. Preoperative coma and bilateral absence of pupillary responses were associated with higher mortality rates. Survivors often achieved functional independence.